Contribution of Educational Management to Optimal Service of Educational Development - Suharsimi Arikunto (Universitas Ahmad Dahlan, 2013)
Education has a momentous and influential role in developing this country. The specific function of educational management may not be fully depended on the central government. In line with local autonomy era, local government (municipality) must also be able to initiate and play its extended role in order to enhance the educational quality at the local level. On the other hand the existence of higher education institutions at local levels, in particular those offering educational management or concentration on educational policy management, have to be able to develop their competencies to collaborate with the municipal educational offices towards further development and improvement of the educational quality at the local levels. This paper will explain several ways that can be done by the Educational Management or Administration in collaboration with the Municipal Educational and Cultural Office to initiate and play its extended role in order to enhance the educational quality at the local level.